(untitled) (Bangladesh Journal of Medical Microbiology, 2013)
Rapid diagnostic tests (RDTs) address the need for accurate diagnosis of malaria, particularly in resource limited settings. In this study, two malaria RDTs were compared with gold standard microscopy: On Site Pf/Pv test detecting Plasmodium falciparum-specific histidine rich protein-2 (Pf HR P2) and P. vivax-specific parasitic lactate dehydrogenase (pLDH) antigens; and SD Bioline anti-Pf/Pv test detecting anti-HR P2 and anti-pL DH antibodies for the diagnosis of P. falciparum and P. vivax infections, respectively. For OnSite test, the overall sensitivity was found 96.2% , specificity 98.2% , positive predictive value (PPV ) 98.2% , negative predictive value (NPV ) 96.4% and agreement with microscopy was found to be 0.94. On the other hand SD Bioline test, the overall sensitivity was 75.4%, specificity 83.7%, PPV 84.3% , NPV 74.5% and agreement with microscopy was 0.59. These data revealed that the R DT based on antigen detection (Onsite test) was more reliable than that based on the antibody detection (SD Bioline test). DOI: http://dx.doi.org/10.3329/bjmm.v5i2.16931 Bangladesh J Med Microbiol 2011; 05 (02): 11-15